Outcomes of stereotactic body radiotherapy 60 Gy in 8 fractions when prioritizing organs at risk for central and ultracentral lung tumors - Zhao, Yizhou (Radiat Oncol, 2020)
BACKGROUND: For stereotactic body radiotherapy (SBRT) to central (C) and ultracentral (UC) lung tumors, our provincial practice has been to prioritize organs at risk (OARs) constraints by compromising target volume coverage if needed. The objectives are to report the treatment’s efficacy and safety. METHODS: We conducted a retrospective analysis of all provincial patients who underwent SBRT at 60Gy in 8 fractions to C and UC lung tumors, from 2013 to 2017. RESULTS: Ninety-eight lesions were treated, 57 (58.2%) C and 41 (41.8%) UC. The median follow-up was 22.9 months (range 2.5–64.8 months). The 1- and 3-year local control (LC) was 97.8 and 84.5% respectively, with no differences between C and UC groups (p = 0.662). Fifty-three (54.1%) cases had optimal dose coverage (V60Gy ITV&PTV > 95%), 29 (29.6%) had compromised PTV coverage (V60Gy ITV > 95%/PTV < 95%), and 16 (16.3%) had both compromised ITV and PTV coverage (V60Gy ITV&PTV < 95%). No significant difference in LC was detected at 2 years between the 3 groups (95.6, 91.8 and 90.9%, p = 0.717). There were 3 episodes of grade 3 toxicity in the C group (2 dyspnea, 1 pneumonitis) and 2 in the UC group (1 dyspnea, 1 hemoptysis). There were no gr4/5 toxicities. On multivariable Cox regression analysis, ITV size was found to be a predictor for LC (p = 0.001). CONCLUSIONS: SBRT at 60Gy in 8 fractions achieves high rates of LC with low risks of significant toxicities, even if target volume coverage is reduced to meet OARs constraints.